2020
DOI: 10.3390/molecules25204846
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Fibrillated Cellulose in Adhesive Systems for the Production of Wood-Based Panels

Abstract: Micro-Fibrillated Cellulose (MFC) is a new type of bio-based additive, coming from wood cellulose. It can compete and substitute oil derived chemicals in several application fields. In the present work, the use of micro-fibrillated cellulose, in waterborne adhesive systems applied in the manufacture of composite wood-based panels was evaluated. Research was conducted to test the potential of improving the performance of wood-based panel types such as particleboard, waferboard or randomly-oriented strand board … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Although the most common residual product is Kraft lignin, obtained by the Kraft process [61], hydrolysis lignin, derived by enzymatic hydrolysis process, contains a certain amount of cellulose. Cellulose in hydrolysis lignin increases the contact areas between lignin and wood fibres, which leads to the formation of additional hydrogen and other bonds [62][63][64][65]. The aim of the present study was to fabricate eco-friendly dry-process fibreboards using hydrolysis lignin as a main binder by modifying the adhesive system and optimising the hot-pressing regime, without any modifications of the lignin.…”
Section: Introductionmentioning
confidence: 99%
“…Although the most common residual product is Kraft lignin, obtained by the Kraft process [61], hydrolysis lignin, derived by enzymatic hydrolysis process, contains a certain amount of cellulose. Cellulose in hydrolysis lignin increases the contact areas between lignin and wood fibres, which leads to the formation of additional hydrogen and other bonds [62][63][64][65]. The aim of the present study was to fabricate eco-friendly dry-process fibreboards using hydrolysis lignin as a main binder by modifying the adhesive system and optimising the hot-pressing regime, without any modifications of the lignin.…”
Section: Introductionmentioning
confidence: 99%
“…Microfibrillated cellulose (MFC) has been used recently as a reinforcement agent in wood adhesives because of its high surface area, stiffness, and strength together with a relatively low density (Guigo et al 2014). The partial replacement of UF and melamine ureaformaldehyde (MUF) adhesive by MFC in single-layer particleboards showed a significant increase in internal bond strength, with almost no change in water related properties and static bending behaviour of panels (Karagiannidis et al 2020). The cited authors showed that a UF adhesive with 5%, 10%, and 20% MFC for plywood panels led to a significant increase in static bending properties.…”
Section: Introductionmentioning
confidence: 99%
“…Lignin [ 7 , 8 , 9 ], tannins [ 10 ], proteins [ 11 , 12 ], and starch [ 13 , 14 ] have been evaluated as raw materials to synthesize the substitutes for existing thermosetting adhesives. Similar to starch, polysaccharides such as cellulose and hemicelluloses are renewable feedstocks for the preparation of bio-based wood adhesives [ 15 , 16 , 17 , 18 ] due to the advantages of being abundant, inexpensive, and environment-friendly. However, the use of cellulose or hemicelluloses to prepare wood adhesives is rarely reported, mainly because cellulose and hemicelluloses do not show any adhesion properties, even at high temperatures.…”
Section: Introductionmentioning
confidence: 99%